Theoretical Analysis and Experimental Study of Subgrade Moisture Variation and Underground Antidrainage Technique under Groundwater Fluctuations - Liu Jie; Hailin Yao; Pan Chen; Zheng Lu; Xingwen Luo (Journal of Applied Mathematics)
Groundwater is a main natural factor impacting the subgrade structure, and it plays a significant role in the stability of the subgrade. In this paper, the analytical solution of the subgrade moisture variations considering groundwater fluctuations is derived based on Richards’ equation. Laboratory subgrade model is built, and three working cases are performed in the model to study the capillary action of groundwater at different water tables. Two types of antidrainage materials are employed in the subgrade model, and their anti-drainage effects are discussed. Moreover, numerical calculation is conducted on the basis of subgrade model, and the calculate results are compared with the experimental measurements. The study results are shown. The agreement between the numerical and the experimental results is good. Capillary action is obvious when the groundwater table is rising. As the groundwater table is falling, the moisture decreases in the position of the subgrade near the water table and has no variations in the subgrade where far above the table. The anti-drainage effect of the sand cushion is associated with its thickness and material properties. New waterproofing and drainage material can prevent groundwater entering the subgrade effectively, and its anti-drainage effect is good.